Pengaruh Lokasi dan Citra Sekolah Terhadap Keputusan Siswa Memilih Sekolah (Studi Kasus di SMA Katolik Rex Mundi Manado) - Ricaldo G. W. Larumpaa; Edwin Wantah; Aneke A. Salam (Indo Publishing, 2026)
The purpose of this research is to determine the impact of location and reputation on students' school choices (Case Study at Rex Mundi Catholic High School Manado). This research uses a quantitative approach and uses primary data through distributing questionnaires to students at Rex Mundi Catholic High School Manado. The results of the research obtained a multiple linear regression equation Ŷ = 2.523 + 0.557 X₁ + 0.462 X₂. Since the t-test results prove that using partial variables the location of the school has a significant impact on students' school choices using the calculated t value > t table is (3.486 > 1.984), the reputation of the school has a significant impact on students' school choices using the calculated t value > t table is (2.889 > 1.984). Then since the F-test results prove that the location of the school and the reputation of the school simultaneously have a significant impact on students' school choices at Rex Mundi Catholic High School Manado using the calculated F value is quite large since F table is (59.23 > 3.09) using a significance value of 0.000 < 0.05. Based on the analysis, it can be concluded that school location and reputation have a significant impact, both partially and simultaneously, on students' choices in choosing a school at Rex Mundi Catholic High School in Manado.